2008
DOI: 10.1117/12.807741
|View full text |Cite
|
Sign up to set email alerts
|

The plasma experiment of the YH-1 mission

Abstract: The Sino-Russian Joint Mars-Phobos Exploration program provides unique opportunity to investigate the global structure of the solar wind/Mars interaction region. The Mars orbiter YH-1 will carry a plasma package consisting of two identical ion detectors, and one electron detector, which is aimed at monitoring the plasma with energy up to a few keV in the environment of the planet, provides a mass analysis of the ions in the mass range form 1 to 44 au. Together with the magnetic field experiment on board YH-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…It has been indicated that intramedullary nail fixation is the preferred choice for treating femur fractures if complete weight bearing is a consideration. [3][4][5][6][7][8][9][10] The present study shows the treatment of Femoral fracture using an intramedullary nailing device which was designed and manufactured by Kaulmed private limited, India.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that intramedullary nail fixation is the preferred choice for treating femur fractures if complete weight bearing is a consideration. [3][4][5][6][7][8][9][10] The present study shows the treatment of Femoral fracture using an intramedullary nailing device which was designed and manufactured by Kaulmed private limited, India.…”
Section: Discussionmentioning
confidence: 99%
“…The Goldstein scores reflect the theoretical impact of events on the promotion or division of geopolitical relations between two countries and are commonly employed for quantitatively assessing political cooperation or conflict. Scholars often consider them as a significant indicator for studying the political and economic relationships between two nations [35,36]. The event impact is based on the quantity of cooperation or conflict events, Goldstein scores, and the number of relevant news reports in the research area, representing the level of impact between countries in terms of cooperation or conflict events during the study period.…”
Section: Event Impactmentioning
confidence: 99%